Provisions for Entitlement to Wages when Benefits are not Satisfied Contemporary Applications in Judicial Rulings Kuwait as a Model: أحكام استحقاق الأجرة عند نقص استيفاء المنافع وتطبيقات معاصرة في الأحكام القضائية دولة الكويت نموذجاً - Badr Al-Uthman, Abdullatif (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
يحتوي البحث على دراسة مشروعية إنقاص الأجرة في العقود المستمرة من خلال أحكام وضع الجوائح في الشريعة الإسلامية مقارنة بالقانون التجاري في دولة الكويت، وتتضمن الدراسة أيضاً الحديث عن علاقة الأجرة بالمنفعة والإلزام في التعاقد، وبيان نظرية الظروف الطارئة، وما يترتب على ذلك من الإلزام في دفع الأجرة كاملة، كما يحدث في وقت إغلاق المحلات التجارية كإجراء احترازي صحي من الحكومة، لتخفيف الوباء المنتشر، وكيف يلزم المستأجر بآثار العقد وهو غير قادر على الانتفاع الكامل؟ خصوصا أن فترة الإجراءات الاحترازية قد وصلت لعدة أشهر، وتراكمت الديون والخسائر على الطرفين، وقد ظهرت أحكام قضائية في المحكمة بإنقاص أجرة العقار في فترة الإغلاق الحكومي، وهنا سيتم المقارنة بين أحكام الشريعة الإسلامية، والقانون التجاري، والأحكام النهائية في مشروعية إنقاص الأجرة. Abstract The research contains a study of the legality of reducing wages in continuous contracts through the provisions of the status of pandemics in Islamic Sharia compared to commercial law in the State of Kuwait. The study also includes discussion about the relationship of wages to benefit and obligation in contracting, and a statement of the theory of emergency conditions, and the consequent obligation to pay the full rent, as happens at the time of closing the shops as a health precaution from the government, to mitigate the spreading the epidemic, and how does the tenant obligate the effects of the contract when he is unable to fully benefit? Especially since the period of precautionary measures has reached for several months, and debts and losses have accumulated on both parties, and judicial rulings have appeared in the court to reduce the rent of the property during the period of government closure, and here the comparison will be made between the provisions of Islamic Sharia, the Commercial Law, and the final rulings on the legality of reducing the rent.